2018
DOI: 10.2196/jmir.9139
|View full text |Cite
|
Sign up to set email alerts
|

A Tailored Web-Based Intervention to Improve Parenting Risk and Protective Factors for Adolescent Depression and Anxiety Problems: Postintervention Findings From a Randomized Controlled Trial

Abstract: BackgroundDepression and anxiety disorders in young people are a global health concern. Parents have an important role in reducing the risk of these disorders, but cost-effective, evidence-based interventions for parents that can be widely disseminated are lacking.ObjectiveThis study aimed to examine the postintervention effects of the Partners in Parenting (PiP) program on parenting risk and protective factors for adolescent depression and anxiety, and on adolescent depression and anxiety symptoms.MethodsA tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 46 publications
4
79
0
Order By: Relevance
“…Male youth were well represented across many studies, constituting more than 50% of the young people in 14 studies (Baker et al, ; Cardamone‐Breen et al, ; DuPaul et al, ; Enebrink et al, ; Hinton et al, ; Irvine et al, ; Jones et al, ; Morawska et al, ; Sanders et al, ; Sanders et al, ; Sourander et al, ; Van Zeijl et al, ; Yap et al, ), on average making up 44.6% of youth participants. In contrast, male caregivers were severely underrepresented (on average 5.0%), with only three studies including more than 10% male caregivers (Khanna et al, ; MacKenzie & Hilgedick, ; Yap et al, ). No male caregivers were primary recipients of the intervention in eight studies (Breitensteinet al, 2016; Fang et al, 2010; Hemdi & Daley, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Van Zeijl et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Male youth were well represented across many studies, constituting more than 50% of the young people in 14 studies (Baker et al, ; Cardamone‐Breen et al, ; DuPaul et al, ; Enebrink et al, ; Hinton et al, ; Irvine et al, ; Jones et al, ; Morawska et al, ; Sanders et al, ; Sanders et al, ; Sourander et al, ; Van Zeijl et al, ; Yap et al, ), on average making up 44.6% of youth participants. In contrast, male caregivers were severely underrepresented (on average 5.0%), with only three studies including more than 10% male caregivers (Khanna et al, ; MacKenzie & Hilgedick, ; Yap et al, ). No male caregivers were primary recipients of the intervention in eight studies (Breitensteinet al, 2016; Fang et al, 2010; Hemdi & Daley, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Van Zeijl et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…No male caregivers were primary recipients of the intervention in eight studies (Breitensteinet al, 2016; Fang et al, 2010; Hemdi & Daley, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Van Zeijl et al, ). In most studies, the majority (>50%) of the sample were educated with post‐secondary qualifications ( n = 14, Baker et al, ; Cardamone‐Breen et al, ; Day & Sanders, ; DuPaul et al, ; Fang et al, ; Hemdi & Daley, ; Jones et al, ; Khanna et al, ; Morgan et al, ; Sanders et al, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Yap et al, ). While most studies did not adequately report the employment status of their participants ( n = 14, DuPaul et al, ; Enebrink et al, 2012; Fang et al, ; Khanna et al, ; Kuravackel et al, ; MacKenzie & Hilgedick, ; Morawska et al, ; Morgan et al, ; Nixon et al, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schinke et al, 2009b; Sourander et al, ; Van Zeijl et al, 2006), of those that did, most reported over 50% of their sample engaged in employed work of some description ( n = 8, Baker et al, ; Cardamone‐Breen et al, ; Day & Sanders, ; Hinton et al, ; Irvine et al, ; Sanders et al, ; Schwinn et al, ; Yap et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further information about the intervention and findings from the follow‐up assessment is available in Yap et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…We used baseline data from both parent and adolescent participants to validate the PSES. Further information about the intervention and findings from the follow-up assessment is available in Yap et al (2018).…”
Section: Methodsmentioning
confidence: 99%